Enhanced Electrochemical Performance of Supercapacitors via Two-Dimensional Indium Sulfide Heterostructure on Carbon Nanotubes - Niraj Kumar; Dhananjay Mishra; Ajit Kumar; Bidyashakti Dash; Rajneesh Kumar Mishra; Junyoung Song; Sung Hun Jin (Applied Sciences, 2023)
This study reports on the synthesis and characterization of a novel electrode material for supercapacitor applications based on a clustered heterostructure of indium sulfide (In2S3) and single-walled carbon nanotubes (SWCNTs). The In2S3-SWCNT (INSC) sample was prepared using the facile successive ionic layer adsorption and reaction (SILAR) method and demonstrated a higher specific capacitance (258 Fg−1 at 1 Ag−1) compared to the bare indium sulfide (In2S3) electrode. The enhanced electrochemical performance is attributed to the synergistic effect between the In2S3 and SWCNTs, which improves electron transportation, catalytic nature, and specific capacitance. Moreover, the cyclic stability of the INSC electrode was significantly improved, retaining 96.8% of the initial capacitance after 3000 cycles. The high voltage holding capacity and high cyclic efficiency of the fabricated INSC-based supercapacitor devices suggest their potential for next-generation energy storage devices. Additionally, the INSC electrode-based supercapacitor devices exhibit excellent flexibility and bendability, retaining similar performance even at a bending angle of 180°, making them suitable for flexible energy storage applications.